Monitoring essential oil quality of Etilingera SP1 GC and GC-MS - Sivanesan, Shanmugam (2008)
Etlingera sp.1 of the family Zingiberaceae is being studied for changes in its essential oil quality during storage. Zingiberaceae comprises about 1200 species of which 1000 is distributed throughout Tropical Asia. Essential oil exists in all species in the genus Etlingera. The highest content is usually in the rhizomes of this plant. Essential oil extracted from the rhizomes is primarily used in fragrance making and have high commercial value due to its antibacterial and therapeutic properties. Suitable extraction method needs to be chosen as essential oils are composed of heatsensitive chemical constituents. In this study, the Clevenger-type hydrodistillation method was employed due to ease of use and milder extracting condition. Essential oil composition was analyzed using GC and GC-MS. Generally, gas chromatographic techniques are used to separate mixtures of chemical constituents into individual components Compounds present were identified using GC-MS while GC was used for weekly analysis. n-Hexane was chosen as solvent as previous studies using n-hexane reportedly produced optimum results. Comparative analysis conducted over a three weeks period indicated that the quality of essential oil exposed to light and temperature underwent minor changes.